competitiveness and development requirements Iraq case study (Journal of the College of Basic Education, 2023)
Talking about the economic aspect of the Iraqi scene and what its future will lead to is consideredThe cornerstone in the study of the Iraqi case, which calls for the withdrawal of factors and the supremacy of some over the other. A cloud that rises above selectivity, but is employed to elect it within the framework of integration with the vocabulary of the report.First of all, we should point out that Iraq has a rich and diversified resource base, as it represents the secondThe world's largest reserves of crude oil, and it has water resources that make it immune from the risks of